2006
DOI: 10.1103/physrevc.74.054601
|View full text |Cite
|
Sign up to set email alerts
|

Determining (n,f) cross sections for actinide nuclei indirectly: Examination of the surrogate ratio method

Abstract: The validity of the Surrogate Ratio method for determining (n,f) cross sections for actinide nuclei is examined. This method relates the ratio of two compound-nucleus reaction cross sections to a ratio of coincidence events from two measurements in which the same compound nuclei are formed via a direct reaction. With certain assumptions, the method allows one of the cross sections to be inferred if the other is known. We develop a nuclear reaction-model simulation to investigate whether the assumptions underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(141 citation statements)
references
References 34 publications
6
135
0
Order By: Relevance
“…This is different from surrogate applications to (n,f) reactions. In the fission case the G CN χ= f ission (E ex , J, π) are much less sensitive to spin and parity and approximations can be employed which allow for analysis methods that do not require the knowledge of the CN spin-parity distributions [17][18][19][20].…”
Section: Of the Desired Reaction See Eq 2 The Decay Probabilities mentioning
confidence: 99%
“…This is different from surrogate applications to (n,f) reactions. In the fission case the G CN χ= f ission (E ex , J, π) are much less sensitive to spin and parity and approximations can be employed which allow for analysis methods that do not require the knowledge of the CN spin-parity distributions [17][18][19][20].…”
Section: Of the Desired Reaction See Eq 2 The Decay Probabilities mentioning
confidence: 99%
“…While this has a smaller effect on the extraction of fission cross sections [9], the γ-ray emission of the compound nucleus can be quite sensitive to the initial J π distribution [14,15,[17][18][19][20][21]. Therefore, in order to extract (n, γ) cross sections from surrogate data it becomes necessary to take into account the J π distribution of the decaying compound nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…While the applicability of the surrogate reaction approach has been successfully demonstrated for (n, f ) cross sections (e.g. * ota2@llnl.gov [8][9][10][11][12][13]), it has been difficult to determine (n, γ) cross sections (e.g., [14][15][16]). …”
Section: Introductionmentioning
confidence: 99%
“…While the applicability of the surrogate reaction approach has been demonstrated for (n,f) cross sections [8][9][10][11][12], it has been difficult to determine (n,J) cross sections due primarily to the discrepancy in the spin-parity distributions of the compound nucleus created by the (n,J) and the surrogate reaction [13][14][15][16][17]. However, some recent research showed promise for inferring (n,J) cross sections by accounting for spin-parity distribution of the compound nucleus [18].…”
Section: Introductionmentioning
confidence: 99%